Ziswaf Alternatif Instrumen Dalam Penanggulangan Backlog Perumahan Di Indonesia - Mahdi, Muhammad (Postgraduate of Jayabaya University, 2025)
The demand for housing in Indonesia remains significant, but it is not yet supported by adequate availability of housing units. The housing policy direction outlined in the National Medium-Term Development Plan (RPJMN) 2020-2024 has so far fallen short of its intended targets. This is evident in the unmet provision of habitable housing according to RPJMN targets. The housing backlog remains high, with 9.9 million households lacking homes and 26.92 million households living in uninhabitable housing conditions. This study aims to identify the root causes of the suboptimal housing provision and financing, as well as to formulate policy recommendations to optimize housing provision in Indonesia. Based on the USG analysis, the primary issues are the rising cost of land and the limited allocation of the state budget (APBN) for the Housing Loan Liquidity Facility (FLPP). To address the housing backlog, it is essential to select adequate policy alternatives measured by five criteria: efficiency, effectiveness, fairness, political acceptance, and ease of implementation. The analysis, utilizing the AHP (Analytic Hierarchy Process) method and matrix analysis, concludes that the use of waqf land and ziswaf (zakat, infaq, and waqf funds) is aviable policy to tackle the housing backlog in Indonesia